Do marker compounds affect the discrimination of Ficus deltoidea Jack varieties? - Khamsah Suryati, Mohd; Azierah, Azemin; Zhari, Ismail (2015)
Chromatographic fingerprint for authentication have been suggested for herbal extracts and preparation which one of the significant concern in herbal standardization. The comparison of chemical profile of extracts with the reference compounds was performed upon the plant that having the varietal issue, Ficus deltoidea Jack (FD). Vitexin and isovitexin were established marker compounds for FD. The discrimination of FD varieties was explored using chromatographic data in order to identify the effect of marker compounds in the discrimination of FD varieties. A simple, rapid, and reliable separation technique using High Performance Thin Layer Chromatography (HPTLC) has been developed and validated for the investigation of the discrimination among FD varieties. Eight varieties of methanol extract and five varieties of water extract were developed along with reference compounds in solvent system consists of ethyl acetate: formic acid (0.1%): methanol (5:5:2 v/v/v), based on the separation of marker compounds. Multivariate statistical analysis of HPTLC retention factor data was employed using principal component analysis (PCA), hierarchical cluster analysis (HCA) and discriminant analysis (DA). PCA of methanol and water extract were clustered into three groups where PC1 for both extract account for 25.89% and 29.46% of total variance. Methanol and water extracts were 17.69% and 27.07% for PC2. The total variances for methanol and water extracts were 43.58% and 56.53%, respectively. However, natural grouping from HCA give five clusters for methanol extract and three clusters for water extract. Clustering by HCA was further analyzed by discriminant analysis; showing that methanol and water extracts were 100% discriminated. Results shown that the discriminants between FD varieties for methanol were unidentified compounds at Rf value of 0.1, 0.12, 0.23, and 0.72. As for water extract, the main discriminants were vitexin, unidentified compounds at Rf value 0.46 and 0.81. This finding indicates that HPTLC analysis has the potential for the development of a fast and reliable analytical methodology for authentication of plant materials